2015
DOI: 10.1371/journal.pone.0129247
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatitis B, Hepatitis C and HIV-1 Coinfection in Two Informal Urban Settlements in Nairobi, Kenya

Abstract: BackgroundHIV-1 and Hepatitis B and C viruses coinfection is common in Sub-Saharan Africa due to similar routes of transmission and high levels of poverty. Most studies on HIV-1 and Hepatitis B and C viruses have occurred in hospital settings and blood transfusion units. Data on Hepatitis B and C viruses and HIV-1 coinfection in informal urban settlements in Kenya are scanty, yet they could partly explain the disproportionately high morbidity and mortality associated with HIV-1 infections in these slums.Object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
33
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 30 publications
12
33
5
Order By: Relevance
“…Only one patient involved in the study presented with a triple co-infection. This result is similar to the one reported by other authors, thus confirming the scarcity of triple co-infection [16][17][18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Only one patient involved in the study presented with a triple co-infection. This result is similar to the one reported by other authors, thus confirming the scarcity of triple co-infection [16][17][18].…”
Section: Discussionsupporting
confidence: 92%
“…In this research work, HIV/HCV co-infection is low (0.4%). This result is close to the 0.46% rate reported by Kerubo et al in Kenya, and to the 0.7% rate reported by Chiekulie et al in Nigeria among adults [16,17]. Abera et al had reported a higher rate of 5.5% [5].…”
Section: Discussionsupporting
confidence: 88%
“…Prevalence rates of these HBV and HCV co-infections can vary according to the risk factors involved [35]. Such data is not always available in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly endemic in sub-Saharan Africa and East Asia, where approximately 5% to 10% of the adult population is chronically infected (4). In Kenya, the seroprevalence of HBsAg positivity is about 5% to 14% and the prevalence of HBV exposure is 20% to 70% (5,6). For this reason, treatment and follow-up of chronic HBV infection is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular diagnostic methods have been used to quantify the levels of HBV DNA in serum as a marker of viral replicative activity (9). The detection and quantification of HBV DNA is reported to have prognostic value for the outcomes of acute and chronic HBV infections (6). However, HBV DNA quantification assays are molecular-based and expensive (9).…”
Section: Introductionmentioning
confidence: 99%